Anti-Cancer Activity of a Novel Small Molecule Compound That Simultaneously Activates p53 and Inhibits NF-κB Signaling - Hwang, Sun Gwan; Park, Jinah; Park, Joo Young; Park, Cheol Hyoung; Lee, Ki-Ho; Cho, Jeong Woo; Hwang, Jong-Ik; Seong, Jae Young (PLOS ONE, 2012)
The p53 and NF-κB pathways play important roles in diverse cellular functions, including cell growth, apoptosis, and tumorigenesis. Mutations that inactivate the p53 gene and constitutive NF-κB pathway activation are common occurrences in human cancers. Although many drugs are being developed that selectively activate p53 or inhibit NF-κB, there are few drug candidates that can do both. Simultaneous activation of p53 and inhibition of the NF-κB pathway is therefore a prime target for new cancer drug development. This study is the first report of a high-throughput approach with mass compounds that concurrently target both pathways. Using a cell-based screening assay and a library of 200,000 synthetic compounds, we identified 9 small molecules that simultaneously inhibit NF-κB and activate p53. One of these compounds, N-2, increased the expression of p53 target genes, including p21 and GADD45a. In addition, N-2 inhibited the transcriptional activity of NF-κB, concomitantly repressing interleukin-6 and monocyte chemotactic protein-1 (MCP-1) expression. When cell lines derived from a diverse range of cancers were treated in vitro with N-2, we observed increased cell death. N-2 also significantly inhibited allograft growth in murine models of melanoma and lung carcinoma. Our findings suggest that N-2 may act as a bivalent anti-cancer agent through simultaneous modulation of NF-κB and p53 activities.